Integrating the 'genomic mosaic' view of species into studies of biotic interactions: a comment on Bernhardsson et al. (2013). (18th October 2013) - Lexer, Christian; Caseys, Celine; Stritt, Christoph; Whitham, Thomas G.
Abstract: The co‐occurrence of geographical structure in herbivore communities, metabolomes and defence genes in forest trees has been analysed in the context of 'geographical mosaics' of coevolution. A deeper understanding of these important issues will require full integration of a 'genomic mosaic' view of species into community ecology.